2022
DOI: 10.1063/5.0128271
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid perovskites under pressure: Present and future directions

Abstract: Hybrid organic–inorganic perovskites (HOIPs) have emerged as outstanding candidates for high-performance photovoltaic devices, and a large variety of HOIPs has been synthesized with different compositions and structural motifs. However, issues remain about their stability and optimization for applications, motivating studies to provide better insight into understanding the structure-property relationship. The application of pressure has proven to be a valuable tool to reach this goal without altering the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 157 publications
0
8
0
Order By: Relevance
“…The crystal structure of these compounds can be described as an inorganic sub-lattice of corner-sharing PbBr 6 (PbI 6 ) octahedral units hosting the MA molecules . Because of the high compressibility of the inorganic host lattice and the organic molecule, the crystal structure of hybrid perovskites can be easily modified applying an external pressure . In the case of MAPbBr 3 , two phase transitions have been reported below 4.6 GPa. Pressure modifies not only the crystal structure but also the electronic properties, including the band-gap energy, thereby becoming a powerful tool to strengthen the current understanding of the properties of MAPbBr 3 as well as other HOIPs, and to provide information relevant for optimizing the photovoltaic performance .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal structure of these compounds can be described as an inorganic sub-lattice of corner-sharing PbBr 6 (PbI 6 ) octahedral units hosting the MA molecules . Because of the high compressibility of the inorganic host lattice and the organic molecule, the crystal structure of hybrid perovskites can be easily modified applying an external pressure . In the case of MAPbBr 3 , two phase transitions have been reported below 4.6 GPa. Pressure modifies not only the crystal structure but also the electronic properties, including the band-gap energy, thereby becoming a powerful tool to strengthen the current understanding of the properties of MAPbBr 3 as well as other HOIPs, and to provide information relevant for optimizing the photovoltaic performance .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high compressibility of the inorganic host lattice and the organic molecule, the crystal structure of hybrid perovskites can be easily modified applying an external pressure . In the case of MAPbBr 3 , two phase transitions have been reported below 4.6 GPa. Pressure modifies not only the crystal structure but also the electronic properties, including the band-gap energy, thereby becoming a powerful tool to strengthen the current understanding of the properties of MAPbBr 3 as well as other HOIPs, and to provide information relevant for optimizing the photovoltaic performance . Regarding the crystal structure, a recent single-crystal X-ray diffraction study revealed that MAPbBr 3 undergoes two phase transitions following the space-group sequence: Pm 3̅ m → Im 3̅→ Pmn 2 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of behavior suggests that interactions above 7.0 GPa between organic cations and inorganic substructure become so strong that they lead to distortion of both organic cations and PbBr 6 octahedra, as well as increased octahedral tilting. This static disorder was observed in different 3D and some (001)-oriented lead halides. , However, in case of (001)-oriented perovskites, this static disorder was usually observed at larger pressure than in our case, i.e., 9.2 GPa for (C 6 H 5 CH 2 NH 3 ) 2 PbI 4 and 8.2 GPa for (C 6 H 5 CH 2 CH 2 NH 3 ) 2 PbBr 4 . , The static disorder process and pressure-induced phase transition are reversible, as evidenced by reappearance of the bands during decompression and recovery of the ambient pressure phase at 0.01 GPa (Figure S4).…”
Section: Resultsmentioning
confidence: 42%
“…Hence, TE causes a gap reduction. However, lead halide perovskites are an exception in terms of the sign of the gap pressure coefficient (see ref and references therein).…”
Section: Resultsmentioning
confidence: 99%